Network for gliricidia research - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Scientists from Africa, Asia, the Americas and Europe meeting at the Centro Agronomico Tropical de Investigacion y Ensenanza (CATIE) in June 1987, have established a gliricidia research network. Gliricidia sepium is a multipurpose nitrogen-fixing...